2014
DOI: 10.1136/oemed-2014-102378
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical risk factors for carpal tunnel syndrome: a pooled study of 2474 workers

Abstract: Background Between 2001 and 2010, five research groups conducted coordinated prospective studies of carpal tunnel syndrome (CTS) incidence among US workers from various industries and collected detailed subject-level exposure information with follow-up of symptoms, electrophysiological measures and job changes. Objective This analysis examined the associations between workplace biomechanical factors and incidence of dominant-hand CTS, adjusting for personal risk factors. Methods 2474 participants, without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
133
4
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(147 citation statements)
references
References 33 publications
(55 reference statements)
5
133
4
5
Order By: Relevance
“…As CTS has become one of the most frequent causes of work compensation, both in Europe and in the United States, and due to the large and still increasing number of people working with computers, also a feeble excess of risk means that a high number of workers may then experience upper extremities [4,5]. Occupational (i.e., repetitive and forceful work such as gripping, vibrations) and non-occupational risk factors (i.e., female sex, age, obesity, diabetes, gynaecological surgery, menstrual problems/disorders and exercise levels) have been associated with CTS, suggesting a multifactorial aetiology [6][7][8][9][10][11][12][13][14][15]. The controversial association between CTS and visual display unit (VDU) use, suggested since the seventies of the last century, still remains an unsolved issue [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As CTS has become one of the most frequent causes of work compensation, both in Europe and in the United States, and due to the large and still increasing number of people working with computers, also a feeble excess of risk means that a high number of workers may then experience upper extremities [4,5]. Occupational (i.e., repetitive and forceful work such as gripping, vibrations) and non-occupational risk factors (i.e., female sex, age, obesity, diabetes, gynaecological surgery, menstrual problems/disorders and exercise levels) have been associated with CTS, suggesting a multifactorial aetiology [6][7][8][9][10][11][12][13][14][15]. The controversial association between CTS and visual display unit (VDU) use, suggested since the seventies of the last century, still remains an unsolved issue [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, studies on CTS in occupational medicine and, in particular, in VDU workers often lack an accurate evaluation of personal medical history. As CTS is a very frequent condition in adult females [3][4][5], for both anatomical and physiological reasons [1][2][3][4][5], with a very large array of well-established occupational and non-occupational risk factors [6][7][8][9][10][11][12][13][14][15], it should be interpreted as a "work related musculoskeletal disorder," i.e., an impairment of body structures associated with, rather than simply caused by, cumulative exposure to work and working environment over a long period of time [25]. In other words, not only occupational but also personal history influence in probabilistic terms natural history of CTS, both inducing and anticipating its clinical presentation [1,2,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, we found no tendon or joint pathologiesTo explain these relationships in the groups, unlike findings from another recent study. 16 the underlying Pathogenetic mechanisms of increased pain in high smartphone users are not clear. In addition, we found increased pinch strength and grip strength increased with the duration and time of smartphone use, and this may have been due to enlargement of tendons such as The fpl tendon as suggested in another study.…”
Section: Discussion:-mentioning
confidence: 99%
“…8,9 the human hand has unique features and functions like any other organ of the body in everyday life, and the functional impairment of the hand can affect everyday life and ultimately the quality of life.…”
Section: Introduction:-mentioning
confidence: 99%
“…Repetitive joint movements and joint position are the main biomechanical factors that may influence CTS. Moreover, studies suggested occupational biomechanical factors may contribute to workplace CTS incidents (Bao et al, 2015;Dias et al, 2004;Harris-Adamson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%